What Would Become of Nuclear Risk if Governments Changed Their Regulations to Recognize the Evidence of Radiation’s Beneficial Health Effects for Exposures That Are Below the Thresholds for Detrimental Effects? - Jerry M. Cuttler (SAGE Publishing, 2021)
The 1953 Atoms for Peace Speech to the United Nations proposed applying nuclear energy to essential needs, including abundant electrical energy. The widespread fear of ionizing radiation from nuclear facilities and medical procedures began after the United States National Academy of Sciences performed a study of radiation dangers to the human genome. This study, initiated and managed by an oil industry benefactor, recommended in 1956 that the risk of radiation-induced mutations be assessed using the linear no-threshold dose-response model instead of the threshold model. It was followed by a study that wrongly linked low radiation to cancer among the atomic bomb survivors. The ensuing controversy resulted in a compromise. The National Committee on Radiation Protection adopted the precautionary principle policy in 1959, justified by fear of cancer and lack of knowledge. The United States and all other countries followed this recommendation, which remains unchanged 62 years later. Its impact on nuclear energy and medicine has been profound. Many costly regulations have been enacted to prevent very unlikely human or equipment failures—failures that would lead to radiation exposures that are below the dose thresholds for lasting harmful effects. Potential low-dose radiation therapies, against inflammation, cancer, autoimmune, and neurodegenerative diseases, are shunned.